2005
DOI: 10.1038/sj.bjp.0705981
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of modifying RyR‐activating peptides for membrane permeability

Abstract: 1 Our aim was to determine whether lipoamino acid conjugation of peptides that are high-affinity activators of ryanodine receptor (RyR) channels would (a) render the peptides membrane permeable, (b) alter their structure or (a) reduce their activity. The peptides correspond to the A region of the II-III loop of the skeletal dihydropyridine receptor. 2 The lipoamino acid conjugation increased the apparent permeability of the peptide across the Caco-2 cell monolayer by up to B20-fold. 3 Nuclear magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Lipidation of ryanodine receptor agonist [D-Arg 18 ]peptide A2 (Fig. 10b) with LAA maintained peptides' α-helical structures, increased peptides' Ca 2+ release activities and permeabilities across the Caco-2 cell monolayers as compared to that of the native peptide [62]. LAA conjugations enhanced the serum stability of thymopentin TP5 (RKDVY, Fig.…”
Section: Lipoamino Acids (Laas)mentioning
confidence: 95%
“…Lipidation of ryanodine receptor agonist [D-Arg 18 ]peptide A2 (Fig. 10b) with LAA maintained peptides' α-helical structures, increased peptides' Ca 2+ release activities and permeabilities across the Caco-2 cell monolayers as compared to that of the native peptide [62]. LAA conjugations enhanced the serum stability of thymopentin TP5 (RKDVY, Fig.…”
Section: Lipoamino Acids (Laas)mentioning
confidence: 95%
“…So far, we have shown that attaching lipid tails to the A peptides shown in Fig. 8 substantially increases the membrane permeability of the compounds and, in fact, enhances their interactions with RyRs, 80 but the modified peptides have a deleterious effect on membrane potential. We are now using a different approach with synthetic compounds that mimic peptide structure.…”
Section: An Explosion Of Information Between 1990 and 2005mentioning
confidence: 94%
“…An attractive and feasible route for the pharmacological modulation of RyR2 may include the use of recombinant proteins or small synthetic peptides that target specific functional epitopes within RyR2 to stabilise the channel [18,74,75,122]. Since this approach confers sequence-specific interaction, and thus can be tailored to numerous intra-RyR2 targets, it offers the potential ability to modulate discrete aspects of RyR2 function.…”
Section: Ryr2-targeted Anti-arrhythmic Therapies a Pharmacological Mmentioning
confidence: 99%